Hubungan Pemberian Asi Eksklusif Dan Pola Asuh Terhadap Status Gizi Balita Usia 6-24 Bulan Di Puskesmas GODEAN I - Aulia Afita Sari; Evi Wahyuntari (CV. ITTC INDONESIA, 2024)
Nutritional problems in Indonesia cause more than 80% of child mortality. One of the efforts that can be done to improve or repair nutrition in infants is by providing exclusive breastfeeding. Parenting patterns can indirectly affect nutritional status. Mothers with good parenting patterns will have toddlers with good nutritional status. The study aims to determine the correlation between exclusive breastfeeding and parenting patterns to the nutritional status of toddlers aged 6-24 months. The research design in this study applied cross-sectional method, and the sampling technique used cluster random sampling with a sample size of 58 respondents. The research instruments used was an exclusive breastfeeding questionnaire, a parenting questionnaire, and anthropometric data. The data were analyzed by using the chi-square test. The results of the study showed that the p value was 0.001, which means <0.05, meaning that there is a relationship between exclusive breastfeeding and the nutritional status of toddlers. The OR value was 9.167, which means that exclusive breastfeeding tends to have a good nutritional status for toddlers. The results of the study showed that the p value was 0.035, which means <0.05, meaning that there is a relationship between parenting patterns and the nutritional status of toddlers. The OR value was 6.450, which means that good parenting patterns tend to have a good nutritional status for toddlers. It can be concluded that there is a correlation between exclusive breastfeeding and parenting patterns and the nutritional status of toddlers aged 6-24 months at Puskesmas (Community Health Center) Godean I.